Bridging the Digital Chasm: Infrastructure, Policy, and Personnel Determinants of Network Management in Resource-Constrained HEIs: A Quantitative Study from the Southern Philippines - Hayudini, Mudzramer; Abdulkamal Abduljalil; Fahra Sahibad; Adzlan Hamsaji; Datu Al-Mujiv Kiram (Open Access Indonesia Journal of Social Sciences, 2025)
The digital divide in higher education, particularly in resource-constrained environments, critically impedes institutional effectiveness and academic parity. Effective network systems management (NSM) is the bedrock of modern pedagogy and administration, yet its key determinants are insufficiently understood in these challenging contexts. This study investigates the factors predicting the quality of NSM in public Higher Education Institutions (HEIs) within a geographically isolated and developing region. A quantitative, cross-sectional study was conducted at three public HEIs in Sulu, Philippines, a representative resource-constrained archipelagic province. A validated survey instrument was administered to a stratified sample of 256 respondents, including IT personnel, administrators, faculty, and students. The instrument measured three latent constructs identified from the literature: IT Governance and Policy (ITGP), Technical Infrastructure and Configuration (TIC), and Human Capital and Personnel (HCP). Data were analyzed using descriptive statistics, ANOVA, and multiple linear regression. The overall quality of NSM was found to be 'moderately satisfactory' (M=2.84, SD=1.05), but with a statistically significant and profound chasm between institutions (p < 0.001). Institution 3 (M=1.50) was 'unsatisfactory,' while Institution 2 (M=3.53) achieved a 'satisfactory' status. The multiple regression model was significant (F(3, 252) = 188.7, p < 0.001), explaining 68.9% (Adjusted R²) of the variance in NSM. IT Governance and Policy emerged as the most powerful predictor (β = 0.45, p < 0.001), followed by Human Capital and Personnel (β = 0.31, p < 0.001). Technical Infrastructure and Configuration (β = 0.18, p < 0.01), while significant, had the smallest unique contribution. In conclusion, the study demonstrates that institutional policy and human capital are more critical determinants of effective network management than technical infrastructure alone. Bridging the digital chasm in resource-constrained HEIs requires a holistic, socio-technical approach, prioritizing the development of robust IT governance frameworks and investing in the continuous training, retention, and empowerment of skilled IT personnel.